THE EFFECT OF PERFORMANCE MANAGEMENT CHARACTERISTICS ON GOVERNMENT APPARATUS PERFORMANCE - Erina Sudaryati; Dhikawidya Nugraha (Berkala Akuntansi dan Keuangan Indonesia, 2019)
The decline or low public confidence in government institutions is a fundamental problem in Indonesia as well as in developed countries. The decline of trust occurred among others due to the rampant corruption cases conducted by public officials and non-conformity of services provided to the expectations of the community. To overcome this it is necessary to make efforts by the government to restore public confidence in government institutions. Implementation of performance management system can be one of the efforts to improve the performance of the apparatus and restore public confidence in government institutions. An effective performance management system should be supported by the characteristics of a good performance management system. This study focuses on the characteristics of performance management system activities and structure of performance management systems. This research uses explanatory quantitative method with sample of 116 employees who work in the Agency of Financial and Development Supervision. The results of the analysis show that the performance management system activities and structure of performance management systems have a significant and positive effect on the performance of the apparatus.